Understanding Payment Switching Behavior to QRIS in Southwest Papua: A Push-Pull-Mooring Study - Hidayah, Nurul; Iriani, Latifah Dian (Jurnal Ekonomi & Studi Pembangunan, 2025)
As the global economy changes, it's important to examine why people in Southwest Papua switch from cash to the Quick Response Code Indonesian Standard (QRIS) system. This region is notoriously behind in infrastructure and human development, so studying this area is crucial to expanding the national economy. This study investigates the variables that influence the switching behavior of users in Southwest Papua toward the Quick Response Code Indonesian Standard (QRIS) digital payment. The study investigates the impact of push factors (e.g., perceived trouble, perceived no record for transaction, and difficult to pay cash in large amounts), pull factors (e.g., perceived convenience, promotional benefits, and time saving), and mooring factors (e.g., habit and switching costs) on the transition from cash to digital payments, utilizing the Push-Pull-Mooring (PPM) framework and transaction cost theory. The research utilizes structural equation modeling to analyze QRIS user's patterns in three regions of Southwest Papua Province: Sorong City, Sorong Regency, and Raja Ampat, by using a stratified random sampling method. The results indicate that the adoption of QRIS is significantly influenced by both push and pull factors, with pull factors playing more prominent role. Switching behavior is also significantly influenced by habit while switching costs exhibit a negative influance but statistically insignificant effect. In an effort to expedite the adoption of digital payments in Southwest Papua, these insights provide policymakers and financial institutions with practical advice. They indicate that strategies that emphasize the convenience and advantages of QRIS over cash are more effective in increasing user adoption.